2009
DOI: 10.1590/s1982-56762009000300010
|View full text |Cite
|
Sign up to set email alerts
|

Elaboração e validação de escala diagramática para avaliação da severidade do mofo cinzento em mamoneira

Abstract: Dentre as culturas oleaginosas, a mamona (Ricinus communis L.) vem se destacando nos programas energéticos, ligados à agricultura familiar, em todo o território nacional. Entre os fatores associados a perdas, encontram-se as doenças, principalmente o mofo cinzento causado por Amphobotrys ricini (N.F. Buchw.) Hennebert (sin. Botrytis ricini N.F. Buchw.). Em regiões com umidade relativa alta e maior pluviosidade, durante o período reprodutivo da mamoneira, foram descritas perdas superiores a 50% (Melhorança & St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
11
0
4
Order By: Relevance
“…Using the PPD scale, the evaluators improved the accuracy levels for severity estimates, as observed by other authors who evaluated dendrophama blight in strawberry (Mazaro et al, 2006), gray mold in castor bean (Sussel et al, 2009), and maize white spot (Malagi et al, 2011). Some studies have shown some variability among evaluators using the same scale; therefore, assessments of accuracy and precision are greatly influenced by the ability of each evaluator to estimate the inherent severity (Nutter Jr. & Schultz, 1995), and can be affected by factors such as the complexity of the severity to be assessed, as for cassava, and as the different types of PPD in their shapes and colors.…”
Section: Resultsmentioning
confidence: 65%
“…Using the PPD scale, the evaluators improved the accuracy levels for severity estimates, as observed by other authors who evaluated dendrophama blight in strawberry (Mazaro et al, 2006), gray mold in castor bean (Sussel et al, 2009), and maize white spot (Malagi et al, 2011). Some studies have shown some variability among evaluators using the same scale; therefore, assessments of accuracy and precision are greatly influenced by the ability of each evaluator to estimate the inherent severity (Nutter Jr. & Schultz, 1995), and can be affected by factors such as the complexity of the severity to be assessed, as for cassava, and as the different types of PPD in their shapes and colors.…”
Section: Resultsmentioning
confidence: 65%
“…() and Sussel et al. (). For finding the reproducibility of assessments between evaluators combined in pairs, we fitted linear regression models of the line between severity levels estimated by seven evaluators, without using the diagrammatic scale in the first access and second access to scale.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these images, seven inexperienced evaluators estimated the severity level, with and without use of the scales for red and yellow coffee cherries separately (Sussel et al. ; Custódio et al. ; Santos et al.…”
Section: Methodsmentioning
confidence: 99%
“…Cada repetição foi composta por um vaso contendo uma planta com racemo tratado. As avaliações foram realizadas em dias alternados, a partir do segundo dia após a inoculação, mensurando-se a incidência de frutos doentes e o percentual de área necrosada em cada racemo com auxilio de escala diagramática (28), até a estabilização dos sintomas.…”
Section: Methodsunclassified